DETEKSI DAN IDENTIFIKASI BARCODE 2D MENGGUNAKAN METODE EKSTRAKSI CIRI GABOR FILTER DAN IDENTIFIKASI CIRI BACKPROPAGATION NEURAL NETWORK - Hepiyana V Runesi; Adriana Fanggidae; Meiton Boru (Universitas Nusa Cendana, 2018)
Barcode is a device in the form of a black and white matrix to represent 1 and 0, which aims in storing information. It is divided into two types, namely 1D and 2D barcodes. The different between them is 1D barcode has black and white bars, while 2D barcode has square shape. The method used in this research is grayscaling, floating and screening comprehensive using flood fill pixel reduction algorithm, the perimeter of objects, extraction feature using gabor filter algorithm, the learning method uses backpropagation neural network algorythm, and the identification process using the feedforward method to backpropagation neural network algorythm. The data used in this research is a data of 2D barcode on each of it amounted to 20 users who are taken from the BBM (Blackberry Messenger) contact, due to the lack of data thus a data of the 2D barcode is cropped for 8 times to be the training data and twice to be the test data. The test is done in three stages which the first data set consists of 10 users, the second one consists of 15 users and the last one consists of 20 users. The result of the testing system for those data sets show that the first data set obtains an accuracy of 100%, the second one obtains 93,33% and the last one obtains 66%.